Think you don't need one? Revitalising the Sheraton Butler : a brand revival strategy for a 5-star hotel. - Boey, Dylan Ming Lon. (2008)
The marketing tool proposed is advertising and the brand icon being the Sheraton Butler. Fusing the research findings from intensive Bulter focus group discussions and guest ethnographic interviews, a foundation was laid in finding that ONE thing about the Bulter Service that will make the Sheraton brand a successful one.